2011
DOI: 10.1074/jbc.m111.248138
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Consumption of Human Milk Oligosaccharides by Infant Gut-associated Bifidobacteria

Abstract: The bifidogenic effect of human milk oligosaccharides (HMOs) has long been known, yet the precise mechanism underlying it remains unresolved. Recent studies show that some species/subspecies of Bifidobacterium are equipped with genetic and enzymatic sets dedicated to the utilization of HMOs, and consequently they can grow on HMOs; however, the ability to metabolize HMOs has not been directly linked to the actual metabolic behavior of the bacteria. In this report, we clarify the fate of each HMO during cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
438
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 400 publications
(459 citation statements)
references
References 48 publications
15
438
2
4
Order By: Relevance
“…32) In contrast, strains belonging to B. breve, B. bifidum, and B. longum, which are frequently found in infant's intestines, 19) all showed gradual growth with GOS-P and utilized the DP2 fraction of GOS-M, consisting mainly of lactose. Asakuma et al demonstrated that B. breve does not decrease HMO concentrations until lactose has been expended, 33) indicating that these infant-borne bifidobacteria are highly adapted to this substrate. At the same time, it is noteworthy that B. breve and B. longum utilized the small DP4 fraction of GOS-P in addition to the major DP3 fraction.…”
Section: Discussionmentioning
confidence: 99%
“…32) In contrast, strains belonging to B. breve, B. bifidum, and B. longum, which are frequently found in infant's intestines, 19) all showed gradual growth with GOS-P and utilized the DP2 fraction of GOS-M, consisting mainly of lactose. Asakuma et al demonstrated that B. breve does not decrease HMO concentrations until lactose has been expended, 33) indicating that these infant-borne bifidobacteria are highly adapted to this substrate. At the same time, it is noteworthy that B. breve and B. longum utilized the small DP4 fraction of GOS-P in addition to the major DP3 fraction.…”
Section: Discussionmentioning
confidence: 99%
“…72,73 Of particular interest to researchers is the ability of Bifidobacterium to metabolize HMOs. Certain HMO show bifidogenic effects in vitro, 72,74 selectively stimulating the growth of certain commensal bacteria often identified in BF infants, such as B. infantis, B. bifidum, B. breve and B. longum. 34,42 Additionally, HMOs also serve as a carbon source for various species of Bacteroides common to the infant GI tract, but do not function as a substrate for other members of the Firmicutes phylum or Bifidobacterium species primarily present in adults, such as B. adolescentis and B. animalis; these microbes lack the enzymatic capacity to break down and consume HMOs.…”
Section: Human Milk Oligosaccharidesmentioning
confidence: 99%
“…infantis, a typical fecal isolate from (breast-fed) infants, encompasses a gene cluster predicted to encode GHs and carbohydrate transporters necessary for the import and metabolism of HMOs (5). This 43-kb gene cluster encodes a variety of predicted or proven catabolic enzymes, such as fucosidases, sialidases, a ā¤-hexosaminidase, and ā¤-galactosidases, as well as extracellular solute binding proteins and permeases that are devoted to HMO metabolism (5,(54)(55)(56). Moreover, the genome of this microorganism contains a complete urease operon predicted to be involved in the utilization of urea, representing an important nitrogen source in milk (5).…”
Section: Figmentioning
confidence: 99%